2016
DOI: 10.1007/s00134-016-4655-2
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolic events in critically ill traumatic brain injury patients

Abstract: Despite mechanical and pharmacological prophylaxis, VTE occurs in one out of every five patients with TBI treated in the ICU. Higher age, greater weight and greater severity of TBI increase the risk. The development of VTE was not associated with excess mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
77
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 33 publications
4
77
1
5
Order By: Relevance
“…Our study revealed that almost half of the VTE events were located in neck and upper extremity veins, and only 2 cases were lower extremity DVTs. This might be an important new finding since many previous studies only examined the lower extremities when screening for DVTs in the ICU . This may also be clinically relevant, since one study of ICU patients revealed that DVTs remote from the legs was associated with increased risk for PE and prolonged ICU LOS …”
Section: Discussionmentioning
confidence: 80%
“…Our study revealed that almost half of the VTE events were located in neck and upper extremity veins, and only 2 cases were lower extremity DVTs. This might be an important new finding since many previous studies only examined the lower extremities when screening for DVTs in the ICU . This may also be clinically relevant, since one study of ICU patients revealed that DVTs remote from the legs was associated with increased risk for PE and prolonged ICU LOS …”
Section: Discussionmentioning
confidence: 80%
“…Moreover, in a study examining the potential antithrombotic benefit of HCQ in patients with anti‐phospholipid syndrome, patients treated with HCQ in addition to standard oral anticoagulant therapy had no increased bleeding events . The trauma literature demonstrates persistently elevated VTE rates despite the use of gold standard therapy via low‐molecular‐weight heparins, suggesting that perhaps targeting the coagulation cascade alone is insufficient in this high‐risk patient population . The addition of platelet inhibition for DVT prophylaxis in trauma has been advocated by some but remains controversial .…”
Section: Discussionmentioning
confidence: 99%
“…56,57 The trauma literature demonstrates persistently elevated VTE rates despite the use of gold standard therapy via low-molecular-weight heparins, suggesting that perhaps targeting the coagulation cascade alone is insufficient in this high-risk patient population. 3,4,[58][59][60][61] The addition of platelet inhibition for DVT prophylaxis in trauma has been advocated by some but remains controversial. [61][62][63] Whether HCQ represents a potential VTE thromboprophylaxis strategy in addition to current standard of care warrants further clinical investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is controversy within the literature regarding the exact nature of hemostatic perturbations after TBI, and evidence exists for the presence of both a hypercoagulable and hypocoagulable state [2]. For example, while the initial head injury often leads to increased bleeding tendency and the exacerbation of hemorrhagic lesions [2,[46][47][48], TBI is also independently associated with an increased risk for venous thromboembolism [49][50][51][52] and ischemic stroke [53][54][55][56][57]. Autopsy studies have also revealed that micro-thrombosis is present in the majority patients who have died from head trauma [58].…”
Section: Hemostatic Disturbance In Tbimentioning
confidence: 99%